The genetic architecture of human brainstem structures and their involvement in common brain disorders - Torbjørn Elvsåshagen (Nature Portfolio, 2020)
The genetic architecture underlying brainstem regions and how this links to common brain disorders is not well understood. Here, the authors use MRI and GWAS data from 27,034 individuals to identify genetic and morphological brainstem features that influence common brain disorders.